Shock Wave Study of the Thermal Dissociations of C3F6 and c-C3F6. II. Dissociation of Hexafluorocyclopropane and Dimerization of CF2 - Cobos, Carlos Jorge (2014)
The thermal dissociation of c-C3F6 has been studied in shock waves over the range 620–1030 K monitoring the UV absorption of CF2. The reaction was studied close to its high-pressure limit, but some high-temperature falloff was accounted for. Quantum-chemical and kinetic modeling rationalized the experimental data. The reaction is suggested to involve the 1,3 biradical CF2CF2CF2 intermediate. CF2 formed by the dissociation of c-C3F6 dimerizes to C2F4. The measured rate of this reaction is also found to correspond to the falloff range. Rate constants for 2CF2 → C2F4 as a function of temperature and bath gas concentration [Ar] are given and shown to be consistent with literature values for the high-pressure rate constants from experiments at lower temperatures and dissociation rate constants obtained in the falloff range at higher temperatures. The onset of falloff at intermediate temperatures is analyzed.